Risk Factors and Consequent Diseases of Atherosclerosis in a Population Treated in a Medical Office - Luis Ángel Felicó Riverón; Georgia Díaz-Perera Fernández; Yomeidis Felicó Riverón (Revista Finlay, 2024)
Foundation: atherosclerosis is a disease of multifactorial origin with great genetic and family dependence, susceptible to aggravation depending on the lifestyle and the influence of the environment on the person. Objective: to describe the prevalence of risk factors and diseases resulting from atherosclerosis and the relationship between them. Method: a descriptive cross-sectional study was carried out from January 2022 to March 2023 in medical office #5 of the Lawton Teaching Polyclinic. The study population consisted of the 349 families belonging to the office. Variables were analyzed: sociodemographic, individual measurements of the physical and anthropometric examination, lifestyles, risk factors and diseases resulting from atherosclerosis. Descriptive statistics and confidence interval estimation of Odds Ratio were used. Results: the family history of arterial hypertension predominated (64.8 %), the most frequent consequent disease was the family history of cardiovascular diseases (11.7 %). Overweight and obesity has the highest risk associated with altered waist circumference; arterial hypertension with type 2 diabetes mellitus; dyslipidemia with family history of dyslipidemia; and type 2 diabetes mellitus with dyslipidemia and with a family history of type 2 diabetes mellitus. Altered waist circumference has the highest risk associated with peripheral arterial disease; high blood pressure with cardiovascular disease and peripheral arterial disease; and diabetes and dyslipidemia with chronic kidney disease. Conclusions: the diagnosis of high blood pressure and cardiovascular diseases predominated. Diabetes, high blood pressure and altered waist circumference had the highest risk associated with most of the health problems studied.